2017
DOI: 10.3892/ol.2017.5985
|View full text |Cite
|
Sign up to set email alerts
|

miR-125b is associated with renal cell carcinoma cell migration, invasion and apoptosis

Abstract: Abstract. MicroRNA (miR)-125b has been identified as deregulated in a number of types of cancer. Previous studies have detected the expression of miR-125b in clear cell renal cell carcinoma (ccRCC) tissues by in situ hybridization and revealed that miR-125b was upregulated in ccRCC tissues, and was associated with recurrence and survival of patients with ccRCC. However, the function of miR-125b in RCC remains unclear. Thus, the expression of miR-125b was detected with quantitative polymerase chain reaction (qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, our data on the frequent hypermethylation of the MIR-125b-1 gene and the hypermethylation linkages with progression and metastasis (Varachev et al, 2018) do not agree with the increased level of this miRNA and its role in promoting cell (Jin et al, 2017). The properties of this miRNA are also ambiguous in other types of cancer, such as breast cancer (Loginov et al, 2018a).…”
Section: Aberrantly Methylated Mirna Genes In Ccrccmentioning
confidence: 56%
“…However, our data on the frequent hypermethylation of the MIR-125b-1 gene and the hypermethylation linkages with progression and metastasis (Varachev et al, 2018) do not agree with the increased level of this miRNA and its role in promoting cell (Jin et al, 2017). The properties of this miRNA are also ambiguous in other types of cancer, such as breast cancer (Loginov et al, 2018a).…”
Section: Aberrantly Methylated Mirna Genes In Ccrccmentioning
confidence: 56%
“…miR-495 was previously described to suppress cell proliferation and migration in RCC [44] and epigenetic regulation of miR-495 was linked to tumor suppression in breast cancer [45]. Moreover, posttranscriptional regulation of TACSTD2 expression by miR-125b as well as promotion of cell migration in RCC has been reported previously [46,47]. Also, functional in vitro and in vivo analyses for TACSTD2 in other human tumor entities like lung adenocarcinoma, HCC and cholangiocarcinoma, consistently demonstrated that silencing of TACSTD2 gene expression results in a significant increase of tumor growth [34] and leads to cell proliferation and migration [33,35].…”
Section: Discussionmentioning
confidence: 90%
“…At present, some studies have suggested that a lot of miRNAs could act as oncogenic miRNAs or tumor suppressor miRNAs to participate in the tumorigenesis and progressions of ccRCC, and they might serve as diagnosic and prognosic biomarkers for ccRCC patients [21][22][23][24]. However, several studies have shown that some miRNAs may play complete contradictor roles in diagnosic and prognosic effects for ccRCC, such as miR-99a [25,26], miR-106a [27,28], miR-125b [21,29], miR-144 [30,31], miR-203 [32,33], and miR-378 [34,35], which might greatly limit their applications into the clinical diagnosis and prognosis for ccRCC patients. Therefore, we should further study the functional roles of miRNAs as potentially diagnostic and prognostic biomarkers for ccRCC, whilst it is also very necessary for expanding the screening of new reliable miRNAs as diagnostic and prognostic biomarkers for ccRCC.…”
Section: Introductionmentioning
confidence: 99%